Low-temperature magnetic behavior of the organic-based magnet Na[FeO₆(C₁₀H₆N)₃] - Dyakonov, V.P.; Zubov, E.; Aksimentyeva, E.; Dyakonov, K.; Piechota, S.; Szymczak, H. (Физика низких температур, 2014)
The static and dynamic aspects of magnetic behavior of the complex of iron with 1-nitroso-2-naphthol
Na[FeO₆(C₁₀H₆N)₃] as a function of temperature, frequency and magnetic field have been analysed. The ac susceptibility
( ac) and dc magnetization (Mdc) were measured over a temperature range of 1.5–200 K in external magnetic
field up to 90 kOe and over a frequency range of 95–2000 Hz. The experimental data indicate the absence of magnetic
long range order in this complex. The magnetization does not reach a saturation in field of 90 kOe at 1.5 K. At
low temperatures, the following characteristic peculiarities of magnetic behavior of complex studied have been
found, namely : cusp-like anomalies in the ac susceptibility and zero field coold (ZFC) magnetization at Tcusp =
= 17 K; frequency dependence of the Tcusp temperature; remanence and time-dependent relaxation of ZFC magnetization.
Attempts were made to compare the ac and Mdc anomalies in complex studied with those of other magnetic
systems. Comparison of characteristic peculiarities of magnetic behavior of the spin-glasses and superparamagnets
was also performed. Although superparamagnetic behavior should not be completely ruled out as an explanation of
the freezing phenomena in sample studied, the analysis of experimental results strongly suggests that the spin-glasslike
behavior is a more consistent explanation.